Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/0363546514554193
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of “Hidden Lesions” of the Extra-articular Biceps After Subpectoral Biceps Tenodesis

Abstract: In approximately 80% of the intra-articular biceps tears evaluated in this study, a "hidden lesion" was observed going beyond the bicipital groove and extending to the distal extra-articular portion. Therefore, the subpectoral portion may be considered the optimal tenodesis site for the complete removal of all hidden biceps lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 32 publications
(48 reference statements)
3
71
0
Order By: Relevance
“…The fixation sites include the osteochondral junction line, intertubercular sulcus, and inferior margin of the pectoralis major. It was later recognized that biceps tendon lesions, including wear and tendonitis, extend distally to the intertubercular sulcus, which incurs postoperative pain after proximal fixation. It has been reported that intertubercular sulcus tenodesis may result in a re‐tear rate of at least 25%, and may result in post‐operative pain, stiffness, and loss of external rotation.…”
Section: Discussionmentioning
confidence: 99%
“…The fixation sites include the osteochondral junction line, intertubercular sulcus, and inferior margin of the pectoralis major. It was later recognized that biceps tendon lesions, including wear and tendonitis, extend distally to the intertubercular sulcus, which incurs postoperative pain after proximal fixation. It has been reported that intertubercular sulcus tenodesis may result in a re‐tear rate of at least 25%, and may result in post‐operative pain, stiffness, and loss of external rotation.…”
Section: Discussionmentioning
confidence: 99%
“…However, this manoeuvre appears insufficient based on the findings in the current study as medial sidewall lesions would be missed. Several recent researches have called into question whether arthroscopy provides an adequate view of the LHBT and bicipital groove [20, 26, 27]. Consequently, when a subscapularis tear is suspected and the SGHL/CHL complex appears normal during arthroscopic assessment, the LHBT in its intertubercular groove and the medial wall of the groove must be checked.…”
Section: Discussionmentioning
confidence: 99%
“…This is predominantly attributed to hidden lesions in the biceps that are not identified during the arthroscopic portion of the procedure. In one study by Moon et al 70% of all LHB tendons had a diseased tendon that extended into the distal 1/3 of the biceps [9].…”
Section: Discussionmentioning
confidence: 99%